Analysis of the nonlinear criteria use for the foods quality assessment - Koretska, Iryna; Deinychenko, Liudmyla; Kravchenko, Tamara (My University, 2020)
The paper presents an analysis of the use of the definition of nonlinear criteria to check the quality of finished products. Comparative calculations of culinary dishes of the main organoleptic indicators and their descriptors showed showed identical results. When determining the priority of prototypes, you can use the calculation of both the qualimetric quality criterion and the calculation of the quality criterion for profilograms.В роботі представлено аналіз використання визначення нелінійних критеріїв для перевірки якості готової продукції. Порівняльні розрахунки кулінарних страв основних органолептичних показників та їх дескрипторів показали показали ідентичні результати. При визначенні пріоритетності дослідних зразків можна використовувати розрахунок як кваліметричного критерію якості, так і розрахунок крітерію якості за профілограмами.
Keywords: foods; quality analysis; priority of samples; rating; готова продукція; зразки; якість; рейтинг; кафедра технології ресторанної і аюрведичної продукції